Polimorfismos no gene receptor da vitamina D (VDR) e a coexistência de periodontite e lúpus eritematoso sistêmico - Soares, Karolyne de Melo (2025)
There are evidences of a shared genetic predisposition between periodontal disease (PD) and systemic lupus erythematosus (SLE), which may explain the association between these conditions. The similarity in their pathogenesis has spurred research aimed at understanding this relationship. Vitamin D, extensively studied in inflammatory diseases, emerges as a relevant marker in the interaction between PD and SLE, particularly in the study of genetic polymorphisms, which are crucial for identifying biomarkers and mapping genes associated with common disorders. This genetic investigation is essential to clarify the signaling pathways between these diseases and to develop personalized therapeutic strategies. In this context, the objective was to identify the association of genetic polymorphisms in the VDR gene for BsmI (rs1544410), FokI (rs2228570), and TaqI (rs731236) with the coexistence of periodontitis and systemic lupus erythematosus. A cross-sectional study was conducted, including laboratory analyses of oral mucosa samples from 181 participants recruited between May 2017 and December 2019. Participants, of both sexes, were allocated into four groups: healthy (n = 57), periodontitis (n = 40), SLE (n = 46), and SLE + periodontitis (n = 38). SLE activity was assessed using the American College of Rheumatology (ACR) guidelines, and periodontal evaluation followed the classification of periodontal diseases. DNA was extracted from saliva, and single nucleotide polymorphisms (SNPs) BsmI (rs1544410), FokI (rs2228570), and TaqI (rs731236) in the vitamin D receptor (VDR) gene were analyzed using the PCR-RFLP technique (Polymerase Chain Reaction–Restriction Fragment Length Polymorphism). Descriptive and inferential statistics were performed, employing Chi-square, Mann-Whitney U, Kruskal-Wallis, Student’s t-test, and one-way ANOVA, with a significance level of p < 0.05. Odds ratios (OR) with their 95% confidence intervals (95% CI) and Hardy-Weinberg equilibrium (HWE) were calculated. The participants' ages ranged from 20 to 71 years, with a predominance of women (77.9%). The frequency of periodontitis diagnosis in stages II and III/IV and SLE activity was similar across groups. The B allele and BB + Bb genotypes of the BsmI SNP were more common in patients with SLE, representing a twofold increased risk for SLE development (OR = 2.0, 95% CI [1.0–3.8], p = 0.04). Conversely, the t allele and Tt + tt genotypes of the TaqI SNP were more frequent in patients with SLE without periodontitis, representing a similar risk factor for SLE (OR = 2.3, 95% CI [1.2–4.4], p = 0.01). No significant association was observed with the FokI SNP. In conclusion, the BsmI polymorphism (B allele and BB + Bb genotypes) is a risk factor for systemic lupus erythematosus independent of periodontitis, whereas the TaqI polymorphism (rs731236) (t allele and Tt + tt genotypes) is a risk factor for systemic lupus erythematosus but not for its coexistence with periodontitis.